2019
DOI: 10.4049/jimmunol.1900117
|View full text |Cite
|
Sign up to set email alerts
|

Tim-4 Inhibits NLRP3 Inflammasome via the LKB1/AMPKα Pathway in Macrophages

Abstract: Nonalcoholic fatty liver disease (NAFLD), characterized by excessive inflammation and lipid deposition, is one of the most common metabolic liver diseases. The expression of NLRP3 inflammasome in macrophages is significantly increased in NAFLD, and its activation aggravates NAFLD greatly. Tim-4, as the phosphatidylserine (PS) receptor, is expressed highly in macrophages, and macrophage Tim-4 inhibits inflammation under various conditions of immune activation. However, the precise role of Tim-4 in NLRP3 inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Furthermore, Tim-4 expression was greatly enhanced by IL-6 or TGF-β, which were highly abundant in tumor microenvironment (19,22,23). Our studies also showed that microenvironment of non-alcohol fatty liver disease increased Tim-4 expression in liver tissues greatly, especially in macrophages (24). These data suggest that Tim-4 is inducible under specific disease conditions.…”
Section: Introduction To Tim-4supporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, Tim-4 expression was greatly enhanced by IL-6 or TGF-β, which were highly abundant in tumor microenvironment (19,22,23). Our studies also showed that microenvironment of non-alcohol fatty liver disease increased Tim-4 expression in liver tissues greatly, especially in macrophages (24). These data suggest that Tim-4 is inducible under specific disease conditions.…”
Section: Introduction To Tim-4supporting
confidence: 60%
“…Furthermore, we revealed that Tim-4 promoted AMPKα phosphorylation depending on LKB1. Tim-4/LKB1/AMPKα interaction triggered autophagy and inhibited NLRP3 inflammasome activation, which might be responsible for NAFLD progress (24). However, we could not exclude whether Tim-4 was involved in lipid metabolism, a possibility that warrants further investigation.…”
Section: Chronic Metabolic Diseasementioning
confidence: 87%
“…Moreover, TIM-1 is a binding site for Ebola virus on T lymphocytes and blocking TIM1-PS interactions reduces viral binding, T-cell activation, and cytokine production 106 . TIM-4 is highly expressed on dendritic cells and macrophages, and TIM-4 on macrophages participates in inflammatory responses 107 . TIM-3 is not expressed on naïve T cells, but it is expressed on fully differentiated Th1 cells 108 .…”
Section: Ps Biologymentioning
confidence: 99%
“…KCs were thought to be the most important hepatic efferocytes with the expression of several different PtdSer receptors, such as T cell immunoglobulin, mucin domain-containing molecule 3 (Tim3), Tim4, macrophage c-mer tyrosine kinase (MerTK), stabilin-1, and stabilin-2 (53). Strikingly, both Tim3 and Tim4 were overexpressed in all detected liver macrophage subsets in methionine-and choline-deficient diet (MCD)-induced NASH mice (55,56). Their absence led to increased production of reactive oxygen species (ROS), IL-1β, and IL-18 in macrophages, concomitant with the aggravation of steatosis and liver fibrosis (55,56).…”
Section: Kupffer Cells-hepatocytesmentioning
confidence: 99%
“…Strikingly, both Tim3 and Tim4 were overexpressed in all detected liver macrophage subsets in methionine-and choline-deficient diet (MCD)-induced NASH mice (55,56). Their absence led to increased production of reactive oxygen species (ROS), IL-1β, and IL-18 in macrophages, concomitant with the aggravation of steatosis and liver fibrosis (55,56). Further studies are urgently needed to explore that how those PtdSer receptors participate in efferocytosis mechanisms of macrophages during NASH development.…”
Section: Kupffer Cells-hepatocytesmentioning
confidence: 99%